2020
DOI: 10.1038/s41467-020-14893-x
|View full text |Cite
|
Sign up to set email alerts
|

NMT1 and NMT2 are lysine myristoyltransferases regulating the ARF6 GTPase cycle

Abstract: Lysine fatty acylation in mammalian cells was discovered nearly three decades ago, yet the enzymes catalyzing it remain unknown. Unexpectedly, we find that human N-terminal glycine myristoyltransferases (NMT) 1 and 2 can efficiently myristoylate specific lysine residues. They modify ADP-ribosylation factor 6 (ARF6) on lysine 3 allowing it to remain on membranes during the GTPase cycle. We demonstrate that the NAD+-dependent deacylase SIRT2 removes the myristoyl group, and our evidence suggests that NMT prefers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(112 citation statements)
references
References 55 publications
5
107
0
Order By: Relevance
“…Increased ER stress is a pro-apoptotic phenomenon previously shown in cells treated with another NMT inhibitor 59 . We postulate the inhibition of myristoylation of the Arf1 GTPase, whether at its N-terminal glycine residue or nearby lysine residue 36 , 37 , interferes with its membrane targeting and impairs vesicle trafficking thereby detrimentally affecting chronic/tonic or antigen dependent BCR signaling. Loss of proper Arf1 functionality at the ER may also explain in part the increase in ER stress marker Bip 60 upon PCLX-001 treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased ER stress is a pro-apoptotic phenomenon previously shown in cells treated with another NMT inhibitor 59 . We postulate the inhibition of myristoylation of the Arf1 GTPase, whether at its N-terminal glycine residue or nearby lysine residue 36 , 37 , interferes with its membrane targeting and impairs vesicle trafficking thereby detrimentally affecting chronic/tonic or antigen dependent BCR signaling. Loss of proper Arf1 functionality at the ER may also explain in part the increase in ER stress marker Bip 60 upon PCLX-001 treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…SFKs, Abl, G α subunits, Arf GTPases, caspase truncated (ct-) Bid, and ct-PAK2 are examples of myristoylated proteins that critically regulate cell growth and apoptosis 23 , 29 – 35 . Recently, NMTs were also shown to be responsible for myristoylation of N-terminally located lysine residues of Arf6 GTPase, thereby adding to their roles in cell signaling 36 , 37 . Because NMTs are essential for the viability of parasites, small molecule inhibitors such as DDD85646 were developed as a T. brucei NMT inhibitor to treat African sleeping sickness 38 .…”
Section: Introductionmentioning
confidence: 99%
“…MYR allows ARF6 to remain on membranes during GTPase cycling [85]. In contrast to the irreversible Gly-MYR, several acyl hydrolases targeting Lys-MYR have recently been described including Sirtuin6, HDAC8, and HDAC11 [82], making Lys-MYR a reversible modification dependent on these specific hydrolases.…”
Section: Roles Of Sirtuins and Hdacs With Lys-myrmentioning
confidence: 99%
“…This implies that Lys-MYR, as with other reversible modifications (i.e., phosphorylation, N-terminal acetylation), might be intimately related to signal transduction and tightly regulated by as yet unknown biotic or abiotic signals. In the case of ARF6, NMT prefers the GTP-bound form of ARF6 while SIRT2 prefers the GDP-bound form, allowing an NMT/SIRT2-ARF6 regulatory axis of the GTPase cycle [85]. The N-terminal Lys-MYR might be part of an N-degron, so an important role of Lys-MYR deacylases could be to ensure protein quality control by preventing intracellular Lys-MYR accumulation [84].…”
Section: Roles Of Sirtuins and Hdacs With Lys-myrmentioning
confidence: 99%
“…Based on this initial compound series, the thiomyristoylated analogs were abandoned due to their apparent selectivity towards SIRT2, which was not surprising based on previous literature. 43,44 A small series of substitutions of the N-terminal functional group were selected based on previous SAR studies and X-ray co-crystal structures, which indicated a high degree of freedom for the selection of functionalities at this position ( Figure S2). 32,35 Based on this series, we proceeded with the 3-phenylpropionyl group (c; Figure 2) and the alkyne-containing group (a, Figure 2, Scheme S6), which is amenable for incorporation of fluorophores or other tags using Cu(I)-catalyzed azide-alkyne Huisgen 3+2 cycloaddition "click" chemistry.…”
Section: Structure-activity Relationship Studymentioning
confidence: 99%